Các nhân tố tác động đến hành vi đổi mới sáng tạo của giảng viên đại học tại Việt Nam - Nguyễn Văn, Chương; Cao Quốc, Việt (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Innovation in education plays an important role in meeting the needs of changing workforce. This study presents a systematic framework to analyze the effect of self-efficacy, culture of openness and learning, and perceived social impact on lecturers’ innovative work behavior at universities in Vietnam. Using a sample of 471 lecturers, the research results show that self-efficacy, culture of openness and learning, perceived social impact have positive impacts on innovative work behavior. The results help universities respond to changing environments more effectively, offering administrative implications to foster innovation. In addition, this research has contributed to the model of innovation.
Keywords: Innovative work behavior; Self-efficacy; Culture of openness and learning; Perceived social impact